PERGESERAN BENTUK DAN MAKNA DALAM PENERJEMAHAN TEKS DRAMA MA'SĀTU ZAINAB KARYA ALI AHMAD BĀKATSĪR - Ulfah Haniyatur Rofi‟ah, Muhammad Yunus Anis (Arabic Literature Department, 2015)
This research discusses the kinds of form and meaning shift in the Ma'sātu Zainab drama text translation. The purposes of this research are to describe the kinds of form and meaning shift in the Ma'sātu Zainab drama text translation. The method used in this research is qualitative descriptive. The data source is Ma'sātu Zainab Zainab drama text written by Ali Ahmad Bākatsīr. The data are collected by non-interactive method. The data analyzing in this research are including: data reduction, data display, conclusion and verification. This research can be concluded as follow: First, forms shift in the translation are caused by structural differences between source language and target language. The forms shift, include morpheme strata shifting, syntax strata shifting, and word category shifting. Second, meaning shift in the translation is caused by the absence of quitely equivalent word between source language and target language. The meaning shift is also caused by the cultural differenciation between source language and the target language. The meaning shift consist of meaning shift from generic meaning into the specific one or vice versa, and the meaning shift which is caused by the cultural differenciation point of view.